How Concentration Influences Technique and Success in Playing Egrang - Rahesti, Nonik; Awang Irawan, Fajar; Bambang Priyono (Universitas Negeri Semarang, 2025)
Playing egrang does not only rely on physicality, it also requires concentration to focus full attention on each movement and maintain balance. Concentration plays an important role in the game of egrang, allowing players to better control their bodies to maintain balance. The purpose of this study is to analyze the contribution of concentration to the success of playing egrang. This study uses quantitative methods with regression correlation design. The samples used in this study were 51 elementary school students in Semarang Regency who had filled out inform consent as a willingness to participate in the study. The data in this study were obtained using ice grid concentration exercise and success test of playing egrang which then the data were processed using SPSS software version 25.0. The results showed that concentration has no contribution to the success of egrang with a contribution value of 4.1%, and with a significance value of 0.153 (p> 0.05), so that the contribution of concentration to the success of egrnag is not significant. This indicates that although concentration is required in the egrang game, this factor is not the main determinant of egrang success. Future research is expected to be able to analyze and identify other factors that can contribute to the success of egrang.